Պոլսոյ «Ճակատամարտ»-ը եւ Յակոբ Օշականը - Դանիէլեան, Սուրէն (Հայաստանի ազգային գրադարան / National Library of Armenia, 2023)
Immediately after the Genocide, the Costantinoplean daily newspaper “Chakatamart” became a platform for national-political issues, where Hagop Oshagan stands out with his positions and a clear artistic and political description. Here, next to the prose stories “When they are little,” “When they are young,” his series “Imperial Triumph” is published. The author of the article presents the main issues that touch both creative history and political evaluations. There are also literary-cultural references that played a role in the literary environment (Artashes Harutyunian, Yervand Otian, Yenovq Armen, later Poghos Snapian, Marc Nichanian and others).
Բանբեր Հայաստանի գրադարանների ։ Գիտամեթոդական հանդես ։ Հատուկ թողարկում / Գլխավոր խմբագիր` Աննա Չուլյան ; Պատասխանատու խմբագիր՝ Հայկանուշ Ղազարյան ․- Երևան ։ «Գիրք» հրատարակչություն , 2023 ․- էջ 34 - 38
Keywords: Գրադարանագիտություն, մատենագիտություն և արխիվավարություն